Isolation, HPLC/UV characterization and antioxidant activity of phenylethanoids from Blepharis edulis (Forssk.) Pers. growing in Egypt - Mohamed Abdel-Ghaffar Ashour (Faculty of Pharmacy, Cairo University, 2012)
In our screening program of the Egyptian wild and cultivated plants for antioxidant compounds, four phenylethanoids were reported for the first time from the wild Egyptian species Blepharis edulis (Forssk.) Pers. family Acanthaceae. The antioxidant activity-guided chemical investigation of the methanolic fraction of the aerial part revealed the presence of verbascoside (1), cis-verbascoside (2), isoverbascoside (3), Leucosceptoside A (4). The HPLC/UV characterization of these compounds is found. The compounds were isolated and purified using silica gel column chromatography and semi-preparative HPLC, the structures were identified and confirmed by UV, ESI-MS, MALDI-MS in addition to one and two dimensional NMR experiments. Antioxidant activities of the main fractions of B. edulis extract were determined using the DPPH radical test.